2017
DOI: 10.1099/jgv.0.000923
|View full text |Cite
|
Sign up to set email alerts
|

A lethal model of disseminated dengue virus type 1 infection in AG129 mice

Abstract: The mosquito-borne disease dengue is caused by four serologically and genetically related flaviviruses termed DENV-1 to DENV-4. Dengue is a global public health concern, with both the geographical range and burden of disease increasing rapidly. Clinically, dengue ranges from a relatively mild self-limiting illness to a severe life-threatening and sometimes fatal disease. Infection with one DENV serotype produces life-long homotypic immunity, but incomplete and short-term heterotypic protection. The development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Pathologic changes included splenomegaly with immune reactivity and hepatic focal necrosis. Also, we established similar AG129 models using low passage DENV-4 703-4, DENV-4 TVP-376, and DENV-1 WP/74 infection that develop hallmarks of dengue infection in humans 13 15 . Therefore acute, severe, lethal mouse models are available for the four DENVs.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic changes included splenomegaly with immune reactivity and hepatic focal necrosis. Also, we established similar AG129 models using low passage DENV-4 703-4, DENV-4 TVP-376, and DENV-1 WP/74 infection that develop hallmarks of dengue infection in humans 13 15 . Therefore acute, severe, lethal mouse models are available for the four DENVs.…”
Section: Introductionmentioning
confidence: 99%
“…Of In relation to the hepatic tissue damage reported in humans infected by DENV, most studies have demonstrated some common characteristics of the livers infected with this virus, especially highlighting the presence of necrosis and microvesicular steatosis [12,15,24] . The presence of necrosis is a common finding among studies in both humans and in models of mice infected by DENV and YFV [2,12,15,22,25,26] . Histopathological evidence suggests that severe forms of DENV are determined by the presence of hepatocellular necrosis, usually delimited to zones I and II of hepatic acini [27] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, IRF5 is required for controlling R. parkeri and viral infection (Carlin et al, 2017; Proenca-Modena et al, 2016; Thackray et al, 2014). Lastly, as with R. parkeri , many viruses have increased lethality in Ifnar -/- Ifngr -/- mice (Milligan et al, 2017; Rossi et al, 2016), suggesting a non-redundant protective role for IFN-I and IFN-γ in both types of infection. These similarities are not true for facultative cytosolic bacterial pathogens such as L. monocytogenes, for which IFN-γ is significantly more protective than IFN-I (Rayamajhi et al, 2010).…”
Section: Discussionmentioning
confidence: 95%